ESOL Learners’ Emotional Responses to the Covid-19 Remote Learning Transition: The Influence of Age, Gender, and Language Proficiency - Alomari, Iyad (JOLLT Journal of Languages and Language Teaching, 2024)
The compelled transition of ESOL services to remote learning during the COVID-19 pandemic posed unprecedented learning challenges for learners and instructors, with relatively unexplored psychological impacts. Recognizing and understanding learners’ emotions can assist ESOL teachers, administrators, and students to develop adapted methods and techniques to improve students’ mental health and social-emotional learning, thereby facilitating the learning process. Few studies have investigated ESOL students’ emotional reactions to the transition to remote learning due to the pandemic. This quantitative study provides insight into 156 ESOL learners’ perspectives on their emotional responses to the transition to online learning instructions during COVID-19 school closures. This will help to understand what enhances learners’ success or academic issues to be addressed concerning English skills acquisition. This study seeks to understand learners’ metacognitive challenges and emotional stressors experienced when participating in synchronous online learning during the COVID-19 transition. It also examines factors such as gender, age, and English language proficiency that might affect learners’ attitudes and perceptions of their emotional reactions to the unplanned and quick transitions during the pandemic. College and university students in the US were invited to participate in a five-point Likert scale questionnaire. The findings inform suggested recommendations and implications for improving ESOL synchronous online praxis and creating motivational online learning spaces to support learners’ mental health and learning outcomes.